THE CAUCASUS AS AN OBJECT OF INTERNATIONAL RELATIONS IN RESEARCH WORKS BY V.V. DEGOEV - K. R. Ambartsumyan (Гуманитарные и юридические исследования)
The article deals with the Caucasian discourse of V.V. Degoev. The scholar addresses the Caucasus in the context of international policy of the Russian Empire and provides arguments for justification of joining the region to the Russian Empire. Having analyzed a number of the scholar’s works the author shows theoretical and practical significance of V.V. Degoev’s studies.